Análise do comportamento e a neurociência: uma perspectiva histórica - Souza, Fernando Olga de (2014)
Neuroscience is the scientific study of the neural system, specifically of the human brain (Shepherd, 2010). It was only in the 1960 s with the creation of the Society for Neuroscience in the US, that it became an independent discipline. According to Kandel (2000), during part of the 20th century the study of the brain was shared between the biological and the psychological fields. Neuroscience appeared then as an interdisciplinary field between the two areas of research, interacting with both in a way that its aims of study comprehends from analysis of molecular biology to behavior. It has thereafter a common point with the object of study of the Behavior Analysis. Neuroscience has had great political, scientific, social and economic expansion mainly due to the brain decade project in the US (1990 to 2000). About the relation between Behavior Analysis and other disciplines Malagodi (1986) observes the self sufficiency on the part of the community towards it, while Roediger (2004) speaks about the fact that research in the field has become extremely specific and has led the studies into a deepening in its own field. Considering the expectations left by these two authors the objective of this research was to investigate how the community of the behavior analysts have been drown closer to Neuroscience. Eight important scientific journals on Behavior Analysis have been consulted. The search was divided in three stages using neuroscience terminology in order to verify what has been produced in literature that would relate both disciplines. Seventy nine articles have been found and submitted to analysis: 1) authors, 2) distribution of articles in different journals, 3) the content of the articles and 4) citations to Skinner, the creator of Behavior Analysis. The results showed in general that a large number of authors (179) have published articles on the subject, but few (16) did it more than once. In general, theoretical and experimental researches were more frequent than applied research. Since the 1990 s the number of articles have increased, although it is still small if compared with the great expansion of Neuroscience. The contents of the articles varied a lot and modern neuroimaging technologies were added to more recent research (since 2005). It has been pointed out that part of the community is in favor of this type of research and another part is against it. Authors cited works of different periods of Skinner s career with emphasis on temporal gaps between stimulus and response that, according to Skinner himself, will be fulfill by brain sciences. Finally, some authors consider that the integration with Neuroscience is the key to the survival of the field and the only way to increase its ability to explain behavior. Authors against it argue that Neuroscience is based on hypothetic examples established by cognitivism and to include the finds of Neuroscience are unnecessary for the understanding of behavior